2017
DOI: 10.18632/oncotarget.22219
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs sequencing unveils distinct molecular subgroups of plasmablastic lymphoma

Abstract: Plasmablastic lymphoma (PBL) is an aggressive lymphoma, often arising in the context of immunodeficiency and associated with Epstein-Barr virus (EBV) infection. The most frequently detected genetic alteration is the deregulation of MYC gene through the translocation - t(8;14)(q24;q32). The diagnosis of PBL is often challenging because it has an overlap in morphology, immunophenotype, cytogenetics and virus association with other lymphomas and plasma cell neoplasms; further, its molecular basis remains elusive.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…In addition, Gravelle, P and Laurent, C, et al found that compared with EBV negative PBL, there were abundant leukocyte infiltration and T cell activation signals in EBV positive PBL tissue, high expression of PD-1/PD-L1 immune checkpoint and other immune escape related proteins, and positive correlation with host immunosuppression, suggesting EBV may play a more important role in immune escape [16,28]. In the study of miRNA sequencing in PBL also found that the expression of tumor suppressor gene PTEN, PBX2 and metabolic controller PPARGC1A, PLIN2/adipophilin was regulated by BART-19-5p [24]. These studies suggest that EBV plays an important immunomodulatory role in the development of PBL, during which the latency status of EBV may change, and EBV-miRNAs may be involved in different regulatory roles.…”
Section: Ivyspringmentioning
confidence: 96%
See 1 more Smart Citation
“…In addition, Gravelle, P and Laurent, C, et al found that compared with EBV negative PBL, there were abundant leukocyte infiltration and T cell activation signals in EBV positive PBL tissue, high expression of PD-1/PD-L1 immune checkpoint and other immune escape related proteins, and positive correlation with host immunosuppression, suggesting EBV may play a more important role in immune escape [16,28]. In the study of miRNA sequencing in PBL also found that the expression of tumor suppressor gene PTEN, PBX2 and metabolic controller PPARGC1A, PLIN2/adipophilin was regulated by BART-19-5p [24]. These studies suggest that EBV plays an important immunomodulatory role in the development of PBL, during which the latency status of EBV may change, and EBV-miRNAs may be involved in different regulatory roles.…”
Section: Ivyspringmentioning
confidence: 96%
“…Interestingly, EBV is usually a type I latency in PBL patients, expressing EBNA1, EBERs, and BARTs [16,23]. However, in a recent study of miRNA sequencing in PBL, it was found that EBV also had type II latency in PBL patients and expressed LMP1, suggesting that the latency state of EBV in tumor is not constant, and the change of latency may be related to immune regulation of EBV [24]. PBL patients are often associated with HIV and EBV infection [25,26].…”
Section: Ivyspringmentioning
confidence: 99%
“…Later, it became evident that an EBV infection has an oncogenic role not only in endemic BL (eBL), but also in several other cancers. Considering the scope of this paper, the described entities include eBL, sporadic BL (sBL), HIV-related BL (HIV-BL), Hodgkin lymphoma (HL), plasmablastic lymphoma (PBL), chronic lymphocytic leukemia (CLL), natural killer/T-cell lymphoma (NKTL), diffuse large B-cell lymphoma (DLBCL) of the elderly, HIV-related DLBCL (HIV-DLBCL), post-transplant lymphoproliferative disorder (PTLD), pyothorax-associated lymphoma (PAL), and methotrexate-associated lymphoproliferative disorder (MTX-LPD), among others [ 3 , 6 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Epstein–barr Virus As An Oncovirus In Human Lymphomasmentioning
confidence: 99%
“…Several groups have applied high throughput technologies such as expression microarrays and next generation sequencing (NGS) methods in order to draw the expression patterns of EBV miRNAs in associated tumor samples, patient sera, and cell lines carrying different latency types. Some examples of the studied cancers include BL [ 6 , 9 , 38 , 44 , 45 , 46 , 47 ], HL [ 8 , 38 ], CLL [ 10 ], NKTL [ 11 , 48 ], PBL [ 6 , 38 ], DLBCL (of the elderly and HIV-related) [ 8 ], PTLD (systemic and central nervous system) [ 3 , 49 ], MTX-LPD [ 8 ], PAL [ 8 ], and lymphoblastoid cell lines (LCLs) [ 38 , 50 , 51 ].…”
Section: Ebv-encoded Micrornas In Human Lymphomasmentioning
confidence: 99%
“…The study of miRNA in BL is usually focused on the establishment of miRNA profiles and the understanding of tumor transformation and progression. On this regard, miRNA expression could discriminate BL from other lymphomas, pediatric from adult samples, and Epstein–Barr virus (EBV) BL-positive from negative cases [ 104 , 105 , 106 , 107 , 108 ].…”
Section: Lymphomasmentioning
confidence: 99%